2012
DOI: 10.1007/s00066-011-0050-7
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic LINAC radiosurgery for the treatment of brainstem cavernomas

Abstract: Our results support the role of LINAC-RS as an efficient and safe treatment to significantly reduce the annual hemorrhage rate in patients suffering from brainstem CCMs not eligible to microsurgery. Compared with radiosurgery for arteriovenous malformations (AVMs), the intervention-related morbidity is higher.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…SRS, implemented by Leksell has now become an additional tool [3]. SRS can be delivered modern linear accelerators with stereotactic tools [47]. This study focuses on the results of long-term outcomes with respect to the feasibility, safety and effectiveness of SRS for VS.…”
Section: Introductionmentioning
confidence: 99%
“…SRS, implemented by Leksell has now become an additional tool [3]. SRS can be delivered modern linear accelerators with stereotactic tools [47]. This study focuses on the results of long-term outcomes with respect to the feasibility, safety and effectiveness of SRS for VS.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13] Despite the administration of similar doses, it is reported that the likelihood of sideeffects is higher than those in patients who underwent SRS due to arterial-vascular malformations (AVM). [11][12][13][14] Another potential disadvantage is that the bleeding risk does not disappear until vascular obliteration occurs. Also, a close clinical follow-up is necessary since it is not possible to reveal complete obliteration by angiography.…”
Section: Discussionmentioning
confidence: 99%
“…Certain recent studies have suggested an early application of SRS due to a possible bleeding risk. [6,14] This recommendation is valid in cases with technically unreachable cavernomas who are more likely to have a risk of death due to recurrent bleeding than those due to SRS. In addition to the decrease in the bleeding risk after SRS, a decrease in the seizure frequency has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to these two studies, several studies using linear accelerator-based radiosurgery or Gamma-Knife radiosurgery had been reported (17)(18)(19)(20)(21)(22). Most of these studies reported results regarding the rate of bleeding within 2 years after radiosurgery.…”
Section: Discussionmentioning
confidence: 99%